L’assurabilité des catastrophes naturelles - collaborateurs de la Chaire en assurance de l’Université Laval, Divers (Assurances, 1992)
The authors examine the insurability of natural catastrophes. This article contains excerpts from catastrophe experience in North America, namely from the United States and Quebec. The catastrophes discussed include floods, earthquakes and windstorms (tornados, hurricanes and cyclones.) In fight of the statistics obtained, the authors have concluded that private insurers and government authorities should work together to develop insurance plans for natural catastrophes.